The usefulness of the genetic panel in the classification and refinement of diagnostic accuracy of Mexican patients with Marfan syndrome and other connective tissue disorders - Giovanny Fuentevilla-Álvarez; María Elena Soto; Yazmín Estela Torres-Paz; Sergio Enrique Meza-Toledo; Gilberto Vargas-Alarcón; Nadia González-Moyotl; Israel Pérez-Torres; Linaloe Manzano-Pech; Ana Maria Mejia; Claudia Huesca-Gómez; Ricardo Gamboa (Biomolecules & Biomedicine, 2024)
Marfan syndrome (MFS) is a multisystem genetic disorder with over 3000 mutations described in the fibrillin 1 (FBN1) gene. Like MFS, other connective tissue disorders also require a deeper understanding of the phenotype-genotype relationship due to the complexity of the clinical presentation, where diagnostic criteria often overlap. Our objective was to identify mutations in patients with connective tissue disorders using a genetic multipanel and to analyze the genotype-phenotype associations in a cohort of Mexican patients. We recruited 136 patients with MFS and related syndromes from the National Institute of Cardiology. Mutations were identified using next-generation sequencing (NGS). To examine the correlation between mutation severity and severe cardiovascular conditions, we focused on patients who had undergone Bentall-de Bono surgery or aortic valve repair. The genetic data obtained allowed us to reclassify the initial clinical diagnosis across various types of connective tissue disorders. The transforming growth factor beta receptor 2 (TGFBR2) rs79375991 mutation was found in 10 out of 16 (63%) Loeys-Dietz patients. We observed a high prevalence (65%) of more severe mutations, such as frameshift indels and stop codons, among patients requiring invasive treatments like aortic valve-sparing surgery, Bentall and de Bono procedures, or aortic valve replacement due to severe cardiovascular injury. Although our study did not achieve precise phenotype-genotype correlations, it underscores the importance of a multigenetic panel evaluation. This could pave the way for a more comprehensive diagnostic approach and inform medical and surgical treatment decision-making.